CRISPR/Cas9 Mediated Genome Editing in Crop Plants - Abdulrezzak Memon (Turkish Journal of Agriculture: Food Science and Technology)
Recently, most genomic research has focused on genome editing methods to develop new technologies that could be easy, reliable, and feasible to edit plant genomes for highly productive agriculture. Genome editing is based on alternating a specific target DNA sequence by adding, replacing, and removing DNA bases. This newest technology called CRISPR/Cas9 seems to be less time-consuming, more effective and used in many research areas of plant genetic research. CRISPR/Cas9 systems have many advantages in comparison with ZFNs and TALENs and has been extensively used for genome editing to many crop plant species. Around 20 crop species are successfully worked out for trait improvements, for example, yield improvement, disease resistance, herbicide tolerance, and biotic and abiotic stress management. This review paper will overview recent advances in CRISPR/Cas genome editing research in detail. The main focus will be on the use of CRISPR/Cas9 technology in plant genome research.